ESTIMASI SUMBERDAYA ANDESIT MENGGUNAKAN METODE ORDINARY KRIGING BERDASARKAN PENGUKURAN GEOLISTRIK DI PT. ZLAW GROUP BOYOLALI, JAWA TENGAH - Hendro Purnomo; Rizqi Prastowo; Muhammad Hafizh Hibullah; Setyo Pambudi (Jurnal Teknologi Mineral dan Batubara, 2023)
PT. Zlaw Group Boyolali is a company of andesite mining located in Wates Hamlet, Seboto Village, Gladagsari District, Boyolali Regency, Central Java Province. The potential of andesite in the area is encouraging and the absence of supporting data about the distribution and resources of andesite brings PT. Zlaw Group Boyolali to conducting exploration. The objective of this study is to analyze the interpretation of geoelectric measurements of the dipole-dipole configuration and calculate the volume of andesite resources based on geostatistics optimization at the research location and compare the estimation results with previous studies. The research activity was carried out by measuring 2-dimensional geoelectrical resistivity using a dipole-dipole configuration of 12 passes, which covered 100% of the research area. Based on the results of geostatistics optimization, parameters obtained include: nugget 0.224053, sill 0.641390, range 67.749, major/semi-major 1.188, and major/minor 2.073. Soil volume is 1,245,750 m3 with a tonnage of 3,238,950 tons, a weathered andesite volume of 999,656 m3 with a tonnage of 2,599,106 tons, and fresh andesite volume of 1,437,925 m3 with a tonnage of 3,738,605 tons.